2019
DOI: 10.1055/a-1031-9559
|View full text |Cite
|
Sign up to set email alerts
|

Zeitgerechte Diagnosestellung bei Menschen mit Demenz: der Bayerische Demenz Survey (BayDem)

Abstract: Zusammenfassung Hintergrund Demenzdiagnosen werden häufig erst bei fortgeschrittener Symptomatik gestellt. Die Sicherstellung einer zeitgerechten Diagnose stellt jedoch die Grundlage für die Inanspruchnahme von Therapie- und Unterstützungsleistungen für Menschen mit Demenz (MmD) sowie für deren pflegende Angehörige dar. Bisher haben nur wenige internationale Studien Einflussfaktoren auf die Dauer von den ersten subjektiv wahrgenommenen Symptomen bis zur Diagnosestellung analysiert. Ziel dieser Analyse ist es d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…Implementation as an electronic health record-based registry, where data can be derived directly from clinical data and electronic health records, 65 66 is not purposeful in the early dementia setting. A previous study showed that PWD received their initial diagnosis at an advanced stage of the disease in many cases (16 months after the perception of the first symptoms in median 67 ). Data and knowledge from the disease's preclinical stages are important to understand the disease and slow down the progression.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation as an electronic health record-based registry, where data can be derived directly from clinical data and electronic health records, 65 66 is not purposeful in the early dementia setting. A previous study showed that PWD received their initial diagnosis at an advanced stage of the disease in many cases (16 months after the perception of the first symptoms in median 67 ). Data and knowledge from the disease's preclinical stages are important to understand the disease and slow down the progression.…”
Section: Discussionmentioning
confidence: 99%
“…Des Weiteren erfolgt die Diagnosestellung oftmals erst spät im Krankheitsverlauf. Laut der multizentrischen Längsschnittstudie Bayerischer Demenz Survey – BayDem betrug die mediane Dauer von der Wahrnehmung erster Symptome bis zur Diagnosestellung 16 Monate 4 . Dabei ist eine zeitgerechte Diagnosestellung die Grundlage für die sinnvolle Nutzung von Therapie- und Unterstützungsangeboten 5 .…”
Section: Hintergrundunclassified
“…Point estimates of TSA are typically between 1 and 2 years [25][26][27][28], although the variability is large, and some people wait much longer. Demographic variables such as sex, age, and education seem to be associated with the time until assessment or diagnosis, but the evidence is mixed [29][30][31][32][33][34]. In addition, youngonset dementia typically takes longer to diagnose than late-onset dementia [33,35], and frontotemporal dementia takes longer than Alzheimer's disease or vascular dementia [3,33].…”
Section: Introductionmentioning
confidence: 99%